Changes in Body Weight and Composition Are Associated With Changes in Left Ventricular Geometry and Function in the General Population: SHIP (Study of Health in Pomerania). (March 2017) - Markus, Marcello Ricardo Paulista; Werner, Nicole; Schipf, Sabine; Siewert-Markus, Ulrike; Bahls, Martin; Baumeister, Sebastian Edgar; Völzke, Henry; Felix, Stephan Burkhard; Ittermann, Till; Dörr, Marcus
Abstract : Background—: The different effects of total body weight (TBW), fat-free mass (FFM), and fat mass (FM) on left ventricular (LV) geometry and function are complex. We investigated the associations of changes over time in TBW, FM, and FFM with changes in LV geometry and function. Methods and Results—: We analyzed data from 1189 subjects (694 women), aged 44 to 86 years, from the baseline and the 5-year follow-up examination of the population-based SHIP (Study of Health in Pomerania). TBW was measured, and FFM and FM were calculated based on height-weight models derived from bioelectrical impedance studies. Echocardiographic measurements of LV geometry and function were performed according to the guidelines of the American Society of Echocardiography. Changes in body composition measures were associated with changes in LV geometry and function by multivariable-adjusted linear regression models. A 1-kg increase/decrease in TBW or FM was associated, respectively, with an increase/decrease of 0.89 g or 1.84 g in LV mass, whereas there was no such association on changes in FFM. Moreover, an increase in FM was associated with LV concentric remodeling and impairment of systolic and diastolic function parameters, whereas an increase in FFM was associated with LV eccentric remodeling and improved systolic and diastolic functional variables. Conclusions—: Our findings indicate that changes in LV morphology and function depend on the type of body mass composition. Prospective data need to address whether specific changes in body composition over time may affect the risk for heart dysfunction more precisely than the change in TBW. Abstract : Supplemental Digital Content is available in the text.